THE EFFECT OF SELF EFFICACY, LEARNING MOTIVATION AND STUDENT INVOLVEMENT ON CRITICAL THINKING ABILITIES IN THE ECONOMICS SUBJECT - Marlina, Dina (Universitas Negeri Semarang, 2024)
Critical thinking skills are the basis for analyzing arguments and can develop logical thought patterns and mental activities in terms of solving problems that analyze assumptions, make decisions, and collaborate globally 4C (Critical Thinking, Creativity, Communication, & Collaborative). Very important skills that must be possessed by high school students. This study aims to determine the extent of the influence of self-efficacy, learning motivation, and student involvement on critical thinking skills in the economics subject of SMAN 01 Banjarharjo. This type of research is a quantitative approach research. Causality design. The population in this study were all students of SMAN 01 Banjarharjo majoring in social studies totaling 179 and science totaling 175 and a total of 354 students. Determination of the sample using the Slovin formula with a sample size of 123 respondents. The sampling technique in this study used a random sampling technique. The results showed that self-efficacy and learning motivation had a positive and significant effect on critical thinking skills, while student involvement in learning did not affect critical thinking skills, there was a positive and significant influence of self-efficacy, learning motivation, and student involvement on critical thinking skills. This study concludes that self-efficacy and learning motivation have a positive and significant direct effect on critical thinking skills and student involvement in learning does not have a direct effect on critical thinking skills, self-efficacy, learning motivation and student involvement have a positive and significant direct effect on critical thinking skills. The researcher suggests that students are expected to be able to improve their self-efficacy, learning motivation, and student involvement in critical thinking skills in the economic learning process and students' critical thinking skills, namely students are active in finding problems and solving.